Efektivitas Bahan Ajar Berbasis Kearifan Lokal terhadap Aktivitas dan Hasil Belajar Peserta Didik - Anggi Anggramayeni; Berti Yolida; Rini Rita T. Marpaung (Universitas Lampung, 2018)
This study aims to describe the effectiveness of teaching materials based on local wisdom to increase the activity and learning outcomes of students in SD N 1 Pugung Penengahan on Theme 3